Bentuk Dan Fungsi Tari Remo Putri Soenarto A.S Sebagai Materi Pembelajaran Di Jurusan Tari SMK Negeri 12 Surabaya: Bentuk dan Fungsi Tari Remo Putri Soenarto A.S Sebagai Materi Pembelajaran. - Aulia Mei Eliyanti; retnayu Prasetyanti Sekti (Jurnal Pendidikan Sendratasik, 2024)
This study aims to describe the form and function of the Remo Putri Dance by Soenarto A.S. and its implementation as learning material in the Dance Arts Department of SMK Negeri 12 Surabaya. The Remo Putri Dance is a traditional East Javanese dance form that developed as a welcoming dance and has a dynamic, assertive character, reflecting the cultural identity of the East Javanese people. In the dance learning process, the Remo Putri Dance by Soenarto A.S. was chosen because of its aesthetic and educational value, as well as its movement techniques suitable for developing student skills. This study employed a qualitative research method with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Data sources were obtained from dance teachers, students, and learning documents at SMK Negeri 12 Surabaya. Using the Form Theory from Sumadyo Hadi and the Function Theory from Soedarsono.Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that the Remo Putri Dance by Soenarto A.S. consists of elements of movement, makeup and costume, musical accompaniment, and expressions that depict the character of an agile and dignified woman. The dance movements are dominated by firm movements while still conveying a feminine gentleness. The function of the Remo Putri Dance at SMK Negeri 12 Surabaya is not only as a practical material for learning traditional dance, but also as a means of preserving regional culture, fostering discipline and self-confidence in students, and developing creativity and art appreciation. The results of the study can be concluded that the Remo Putri Dance by Soenarto A.S. has a unique presentation form and educational function that is relevant as learning material in the Dance Department of SMK Negeri 12 Surabaya. This dance plays an important role in supporting the preservation of traditional culture while enhancing students' competencies in the field of dance.